2018
DOI: 10.5539/jsd.v11n3p9
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Consumers Awareness toward Green Products and Its Impact on Purchasing Decision in Bangladesh

Abstract: Consumers’ green products awareness is significant in indicating the way of the green products buying decision. This study aims to investigate the sources of consumers’ awareness toward green products and its impact on purchasing decision. The data is collected from 300 respondents by survey method through a structured questionnaire with five-point Likert scales & multiple items. Convenience and judgmental sampling method are used. Data are analysed using frequency analysis, mean, standard deviation and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 27 publications
(31 reference statements)
3
29
0
Order By: Relevance
“…Consumers' green products consciousness is vital in guiding the buying decisions. The research discovered that green products as a significant factor, which extensively influences consumers buying decisions (Siddique & Hossain, 2018). Producers need sturdy products to defend the product's content form purchaser abuse and physical damage, as well as the flexible outdoor design of the product to survive false lights and climatic excesses at all times.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Consumers' green products consciousness is vital in guiding the buying decisions. The research discovered that green products as a significant factor, which extensively influences consumers buying decisions (Siddique & Hossain, 2018). Producers need sturdy products to defend the product's content form purchaser abuse and physical damage, as well as the flexible outdoor design of the product to survive false lights and climatic excesses at all times.…”
mentioning
confidence: 99%
“…Those massages impact on consumers' awareness and motivate to buy green products (Chang, 2011). The investigation has demonstrated that promotional activities on eco-friendly products and reference groups extensively influence consumers' buying decisions of products (Siddique & Hossain, 2018). Green promotion includes collaborating information on the ecological promises and the efforts made by businesses to consumers (Singh, 2013).…”
mentioning
confidence: 99%
“…The paper aims to examine the sources of general public' consciousness toward green products and its impact on purchasing decision. The study has found that reference groups significantly influence general public green consciousness (Siddique & Hossain, 2018). Therefore, it is anticipated that: H5: Reference groups and green consciousness are positively related to each other.…”
Section: Reference Groups (Rg)mentioning
confidence: 95%
“…affect affirmative intensions to buy green products in America. The inspection has exposed that promotional activities widely influence general public green consciousness (Siddique & Hossain, 2018). Similarly, promotional tools as the notable issues, which influence general public green consciousness.…”
Section: Promotional Tools (Pt)mentioning
confidence: 99%
“…Later many supported the environmental movement and implemented programs that would cause minimum harm to the environment. Green products have less impact on the environment and less damage to human health compared to non-green products [9][10][11][12]. In this paper, the features of green products that influence online consumers is studied.…”
Section: Introductionmentioning
confidence: 99%